(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
As a global medium of connecting and linking across cultures, the internet is quickly gaining interest and attractiveness as the most employed revolutionary marketing tool in the height of the global health crisis due to the COVID-19 pandemic. This scenario inspired this study’s realization to contribute as a guide to online clothing stores for enhancement of customer knowledge and to online fashion retailers for customer persuasion towards purchasing online clothes. The study utilized descriptive research using the survey method involving the 382 sampled online clothes shoppers in the urban barangays of San Fernando City, La Union. The main data gathering tools employed were an adopted and validated survey questionnaire and an unstructured interview to elicit the study’s needed information. The gathered data were treated accordingly using descriptive and inferential statistics. The result showed that online shoppers were mostly female employees aged 21-25 years old and earning an average of Php5000 or above monthly. They had a computer unit and internet access, considered their internet skills as good, and had more years of experience using the internet as opposed to any of the groups who had not made online purchases. Moreover, the study results showed that online shopping is highly influential as to convenience, website design/feature, time-saving, and security concerns. Therefore, entrepreneurs are highly encouraged to consider online selling as an alternative business landscape.